Characteristics of Gut Microbiota and Plasma Metabolites in Patients with Post-Stroke Depression - Yan C; Si T; Zheng W; Huang L; Wen L; Shen H; Qu M (Neuropsychiatric Disease and Treatment)
Chuming Yan,1 Tong Si,2 Wancheng Zheng,1 Liyuan Huang,1 Lulu Wen,1 Huixin Shen,1 Miao Qu1 1Neurology Department, Xuanwu Hospital of Capital Medical University, Beijing, People’s Republic of China; 2Neurology Department, Beijing Shijitan Hospital, Beijing, People’s Republic of ChinaCorrespondence: Miao Qu, Neurology Department, Xuanwu Hospital of Capital Medical University, Beijing, People’s Republic of China, Email qumiao@xwhosp.orgPurpose: The changes in gut microbiota and plasma metabolites have been proposed to play a key role in post stroke depression (PSD), but clinical study based on combined omics is still in lack. This study aimed to investigate the characteristics of gut microbiota and plasma metabolites in patients 3 months after the onset of acute ischemic stroke (AIS), compare PSD and non-PSD groups, and explore possible diagnostic biomarkers.Patients and Methods: Seventy patients with stroke were included at 3 months after AIS onset. Plasma and fecal samples were collected. Gut microbiome was examined using 16S rRNA sequencing, and plasma metabolites were assessed via targeted liquid chromatography-mass spectrometry.Results: Of the 70 patients with ischemic stroke, 25 (35.71%) were diagnosed with PSD. At the genus level, patients with PSD had increased abundance of Parabacteroides, Pyramidobacter, Anaeroglobus, Haliangium, Staphylococcus, CAG− 56, Shuttleworthia, and Epulopiscium, and decreased levels of the Eubacterium eligens group and Prevotella. In patients with PSD, 12 plasma metabolites were altered, with cortisol and pyroglutamic acid levels increased, while 2-phosphoglyceric acid, 3-phosphoglycerate, phosphorylcholine, tryptophan, caffeine, N-methylalanine, ornithine, serotonin, theophylline, and vanillic acid were decreased. Enriched metabolic pathways included glutathione, tryptophan, and caffeine metabolism. Furthermore, significant correlations were observed between gut microbial dysregulation and major plasma metabolite alterations. The areas under the curve values of gut microbiota, plasma metabolites, and the combined dataset for PSD diagnosis were 0.704, 0.875, and 0.940, respectively.Conclusion: This study identified the characteristics of gut microbiota and plasma metabolites as well as a panel of combined biomarkers in 3-month PSD, possibly providing a new theoretical framework for diagnosis and treatment.Keywords: post stroke depression, metabolites, microbiome, biomarkers